Educating all in Laos: Identifying existing inclusive education resources related to children with disabilities - Phannalath, Vikate (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
The idea of inclusive education was introduced to the Lao education system a few decades ago. In 2011, the Lao government passed legislation named the National Policy on Inclusive Education to ensure the right to equitable access to quality education for all people in society. This paper provides information on resources about inclusive education, particularly those including children with disabilities that are available and accessible in Lao. In addition, how inclusive education for children with disabilities has been implemented by relevant partners is discussed. The writer used a literature survey of previous studies, journals, books, legislation, and reports to discuss the existing inclusive education resources in Laos. Some of the information collected regarding inclusive education with a focus on disability inclusion was available in both Laotian and English. These documents are discussed under the headings of (i) specific policies on inclusion of children with disabilities should be made by the relevant authorities, (ii) all pre-service and in-service teachers should receive training on inclusive education for children with disabilities (iii) existing resources should be promoted and disseminated in ways that all people can gain access to, (iv) relevant communities should work together to build stronger partnerships and create the same value of fully including children with disabilities and (v) local community members should be involved in demonstration projects.